Non-Coding RNAs in Glioma Microenvironment and Angiogenesis - Li, Dongxue; Zhang, Zhe; Xia, Chengyu; Niu, Chaoshi; Zhou, Wenchao (Frontiers in Molecular Neuroscience, 2021)
Glioma, especially glioblastoma, is the most common and lethal brain tumor. In line with the complicated vascularization processes and the strong intratumoral heterogeneity, tumor-associated blood vessels in glioma are regulated by multiple types of cells through a variety of molecular mechanisms. Components of the tumor microenvironment, including tumor cells and tumor-associated stromata, produce various types of molecular mediators to regulate glioma angiogenesis. As critical regulatory molecules, non-coding RNAs (ncRNAs) inside cells or secreted to the tumor microenvironment play essential roles in glioma angiogenesis. In this review, we briefly summarize recent studies about the production, delivery, and functions of ncRNAs in the tumor microenvironment, as well as the molecular mechanisms underlying the regulation of angiogenesis by ncRNAs. We also discuss the ncRNA-based therapeutic strategies in the anti-angiogenic therapy for glioma treatment.